Preparation of B/ZnO Nanocomposite by Simple Mechanical Combustion Method for Removal of Antibiotics in Aqueous Environments - Thu Huong Nguyen; Anh-Tuan Vu (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
In this study, the B/ZnO nanocomposite was successfully synthesized by a simple mechanical combustion method. This material was used as a photocatalyst to degrade tetracycline, a representative of the commonly used antibiotics today. The B/ZnO composite became tighter than that of pure ZnO and formed bulk particles. The band gap energy of B/ZnO (3.05 eV) was slightly lower than that of ZnO (3.10 eV), resulting that it being easier to absorb visible light to create electron-hole pairs (h+ and e−). Therefore, the B/ZnO composite had higher photocatalytic activity than pure ZnO. The ratio of boron-doped to ZnO affecting the photocatalysis efficiency was investigated and the optimal boron content was 3 wt%, its degradation efficiency (DE) value for tetracycline hydrochloride (TCH) in 90 min and the rate constants were 90% and 0.054 min−1, respectively. The factors affecting the photocatalytic process like initial antibiotic concentration, catalyst content, and pH of the initial antibiotic solution were studied. In addition, the recovery and reuse of B/ZnO after photocatalytic treatment were also studied. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).